1982
DOI: 10.1159/000137729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbocromene on Ventricular Fibrillation during Acute Myocardial Ischemia in Anesthetized Dogs

Abstract: The effects of carbocromene, 4 mg/kg intravenously, prior to coronary artery occlusion plus 40 μg/kg/min during coronary artery occlusion and reperfusion on ventricular fibrillation threshold (VFT) were studied in pentobarbital-anesthetized open-chest dogs and compared to controls receiving saline. Coronary artery occlusion decreased VFT by 46 ± 4% (mean ± SEM, p < 0.02) in controls and by 22 ± 3 % in drug-treated animals. Reperfusion of the occluded artery decreased VFT by 83 ± 7% (p < 0.01) in controls and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In experimental animals, this instability can be measured by determining the ventricular fibrillation threshold (VFT) [12]. Previous experiments have shown that VFT decreases after acute coronary artery ligation in anaesthetized dogs, and that drugs which offer protective effects can alleviate the VFT reductions [5,11]. It was found in the present study that both ranitidine and cimetidine were effective in preventing the VFT decreases induced by LAD ligation in anaesthetized dogs, indicating their protective effects on ventricular vulnerability in canine hearts during acute coronary artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental animals, this instability can be measured by determining the ventricular fibrillation threshold (VFT) [12]. Previous experiments have shown that VFT decreases after acute coronary artery ligation in anaesthetized dogs, and that drugs which offer protective effects can alleviate the VFT reductions [5,11]. It was found in the present study that both ranitidine and cimetidine were effective in preventing the VFT decreases induced by LAD ligation in anaesthetized dogs, indicating their protective effects on ventricular vulnerability in canine hearts during acute coronary artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular fibrillation (VF) was produced with the technique of Fielder et al [11], with slight modifications. After the pericardium was opened, a plaque of platinum electrodes was sutured to the epicardial surface of the right ventricle near the conus arteriosus.…”
Section: Measurement Of Ventricular Fibrillation Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the 2 h reperfusion period, the LAD was re-occluded, and 1 ml of 1% Evans blue in phosphate-buffered saline was injected into the left ventricle of the beating heart, circulating the accessible vasculature, thereby leaving the area at risk (AAR) unstained (modified from (Fiedler et al, 1982;Ovize et al, 1994). After 2 min with perfusion of Evans blue, the heart was excised and frozen at −80°C overnight.…”
Section: Assessment Of Infarct Sizementioning
confidence: 99%